One-pot three-component synthesis of azaspirononatriene derivatives - Ali Oudi; Abbas Ali Esmaeili; Azizollah Habibi (Scientific Reports)
Abstract The present investigation has introduced a new class of isocyanide/acetylene-based multicomponent reactions (IAMCRs). These are a robust technique for efficiently synthesizing intricate spiro architectures through a zwitterionic adduct. The coupling reaction between the “in situ” generated dipoles of the isocyanide–acetylenic ester adducts and 3-alkyl-4-arylidene-isoxazol-5(4H)-one derivative presents a highly effective synthetic pathway for obtaining novel 1-oxo-2-oxa-3-azaspiro[4.4]nona-3,6,8-triene heterocycles. The broad range of substrates, standard experimental conditions, straightforward procedure, and impressive yields make our catalyst-free three-component approach highly practical and green, as it remarkably offers step-, time- and cost-effectiveness based on the green metrics.